2022
DOI: 10.3390/ma15093124
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Microstructural Evolution of TiNi-Based Intermetallic Alloy with Nb Addition

Abstract: TiNi intermetallic alloys were prepared with 2, 4 and 6 at.% niobium (Nb) addition. The mechanical properties and microstructures of the alloys were investigated under both static (1 × 10−1 to 1 × 10−3 s−1) and dynamic (4 × 103 to 6 × 103 s−1) loading conditions. The intermetallic alloy structures and surface morphologies of the alloys were examined by X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. In addition, the fracture morphologies were observed by optical microscopy (OM). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The addition of elements, for example, Zr, Er, Sc, Zn, Ag and Cu, can upgrade the mechanical performance of Al-Mg-based materials [6][7][8][9]. Researchers have shown that Niobium (Nb) also has the potential to enhance the mechanical performance of some compounds and alloys [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of elements, for example, Zr, Er, Sc, Zn, Ag and Cu, can upgrade the mechanical performance of Al-Mg-based materials [6][7][8][9]. Researchers have shown that Niobium (Nb) also has the potential to enhance the mechanical performance of some compounds and alloys [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%